Tree-ring stable isotopes in cellulose and lignin methoxy groups reveal different age-related behaviour - Wieland, Anna; Römer, Philipp; Torbenson, Max; Greule, Markus; Urban, Otmar; Čáslavský, Josef; Pernicová, Natálie; Trnka, Miroslav; Büntgen, Ulf; Esper, Jan; Keppler, Frank (Quaternary international, 2024)
Tree-ring stable isotopes (TRSI) have the unique ability to capture inter-annual to multi-millennial climate trends and extremes if the appropriate data and methods are combined. However, there is still an ongoing debate about age-related biases in TRSI measurements that potentially affect the fidelity of their chronologies and subsequent climate reconstructions. Here, we investigate carbon and oxygen TRSI measurements in cellulose (δ13Ccell and δ18Ocell) and carbon and hydrogen ratios in lignin methoxy groups (δ13Cmeth and δ2Hmeth) of more than 60 living and relict pine (Pinus heldreichii) trees from northern Greece that span the period 512-2020 CE continuously. We identified significant (p < 0.01) level offsets between living and relict δ18Ocell values (1.49 mUr) that preclude, among others, the combination of living and relict wood series for reliable age-trend assessment, and we found distinct differences between cellulose and methoxy TRSI chronologies including contrasting recent trends in carbon, oxygen, and hydrogen isotope ratios suggesting that varying environmental signals are retained in the TRSI proxies. Assessments are supported by comparisons with well-established ontogenetic trends in tree-ring width and latewood maximum density to identify significant (p < 0.01) age-trends in relict δ18Ocell values between 50 and 190 years of cambial age, and in relict δ13Cmeth and δ2Hmeth values in tree rings older than 100 years. Relict δ13Ccell values, on the other hand, show increasing values between 50 and 80 years of cambial age (p < 0.01), but no evidence for long-term trends beyond these early stages. The combined assessment of multiple TRSI from cellulose and lignin methoxy groups contributes to a better understanding of the underlying physiological processes and extends the range of extractable climate information from the utilized tree-ring proxies. Our findings demonstrate that raw δ13Ccell data from Mt. Smolikas can be used for climate calibration and reconstruction purposes without the need for standardization (expect for rings ≤80 years of cambial age), potentially providing new insights into long-term climate variability in the eastern Mediterranean region. δ18Ocell, δ13Cmeth, and δ2Hmeth values, however, require detrending due to long-term age-related trends.
Online verfügbar: 19. Februar 2024, Artikelversion: 22. Mai 2024
Gesehen am 27.11.2024